Congratulating Klára Gazda - KINDA, ISTVÁN ( NYELV- ÉS IRODALOMTUDOMÁNYI KÖZLEMÉNYEK , 2026)
Author's coordinates: Székely Nemzeti Múzeum, Sepsiszentgyörgy/Sfântu Gheorghe, Kós Károly 10 Email: kindaistvan.sznm@gmail.com Text Complet - PDF (Magyar)